THE APPLICATION OF THE RECITATION METHOD IN IMPROVING STUDENT LEARNING OUTCOMES IN CLASS IX MTS DDI SEPANGE AQIDAH AKHLAK SUBJECT - St Nur Alam (al-Iltizam: Jurnal Pendidikan Agama Islam, 2022)
Abstract:The purpose of this study is to improve student learning outcomes in akidah ahlak subjects in MTs DDI Seppange class IX by using the resitation method. This class action research (PTK) was carried out at MTs DDI Seppange with the research subjects being students in class IX MTs DDI Seppange which amounted to 15 students with details of men totaling 4 people and women totaling 11 students. Class Action Research (PTK) is carried out as many as 2 (two) cycles, each cycle goes through 4 stages, namely planning, action, observation and reflection. This research data was obtained using observation sheets of activities during learning and learning outcomes tests were used to determine the level of student mastery of the subject matter. The data obtained are analyzed using quantitative analysis techniques and qualitative analysis. For quantitative analysis, descriptive analysis is used, namely average and percentage scores. The results showed that the application of the resitation method can improve the learning outcomes of class IX MTs DDI Seppange students as evidenced by an increase in student learning outcomes in the initial test, an average score of 72.33 was obtained with completeness reaching 40%. In the first cycle, it increased with an average score of 82.53 with completeness reaching 80%. And furthermore, in cycle II, student learning outcomes increased with an average score of 85.93 with learning completion reaching 93.33%. Thus, it has met the predetermined performance indicators of 85%, so that the learning outcomes of Class IX MTs DDI Seppange students can be improved through the use of the resitation method on the subject of a commendable attitude towards oneself.Keyword: Resitation Methods, learning outcomes   Abstrak: Tujuan penelitian ini untuk meningkatkan hasil belajar siswa pada mata pelajaran akidah ahlak di MTs DDI Seppange kelas IX dengan menggunakan metode resitasi. Penelitian tindakan kelas (PTK) ini dilaksanakan di MTs DDI Seppange dengan subyek penelitian adalah siswa di kelas IX MTs DDI Seppange yang berjumlah 15 orang siswa dengan rincian laki-laki berjumlah 4 orang dan perempuan berjumlah 11 orang siswa. Penelitian Tindakan Kelas (PTK) ini dilaksanakan sebanyak 2 (dua) siklus, setiap siklus melalui 4 tahapan yaitu perencanaan, tindakan, observasi dan refleksi. Data penelitian ini diperoleh dengan menggunakan lembar observasi kegiatan selama pembelajaran berlangsung dan tes hasil belajar digunakan untuk mengetahui tingkat penguasaan siswa terhadap materi pelajaran. Data yang diperoleh dianalisis dengan menggunakan teknik analisis kuantitatif dan analisis kualitatif. Untuk analisis kuantitatif digunakan analisis deskriptif yaitu skor rata-rata dan persentase. Hasil penelitian menunjukkan bahwa penerapan metode resitasi dapat meningkatkan hasil belajar peserta didik kelas IX MTs DDI Seppange dibuktikan dengan peningkatan hasil belajar peserta didik pada tes awal diperoleh skor rata-rata 72,33 dengan ketuntasan mencapai 40%. Pada siklus I meningkat dengan skor rata-rata 82,53 dengan ketuntasan mencapai 80%. Dan selanjutnya pada siklus II hasil belajar siswa meningkat dengan skor rata-rata 85,93 dengan ketuntasan belajar mencapai 93,33%. Dengan demikian, maka telah memenuhi indikator kinerja yang telah ditetapkan yaitu 85%, sehingga hasil belajar siswa Kelas IX MTs DDI Seppange dapat ditingkatkan melalui penggunaan metode resitasi pada pokok bahasan sikap terpuji terhadap diri sendiri.Keyword: Metode Resitasi, Hasil Belajar